Examining the Effect of Task-Based Language Teaching on University Business Students in Bangkok - Matthew Rudd (IJEE (Indonesian Journal of English Education), 2019)
ABSTRACTThe purpose of this study was to introduce Task-Based Language Teaching in a bid to energise stagnant English language performances among second-year business students (N = 81), studying a private university in the peripheral areas of Bangkok. Students followed a TBLT learning environment for one semester (16 weeks), and subsequent end-of-term performances were compared with prior attainments achieved under tradition forms of instruction using t-tests (0.05). Overall, TBTL proved to positively influence performance outcomes when compared to the traditional method (TBLT: 60.9 = Grade C+; TRAD: 54.93 = Grade C; p [0.0195] = sig <0.05). Nonetheless, the majority of progress derived from enhancements in speaking skills, as assessments in this domain improved significantly, whereas no significant difference was observed in formal examinations. Further to this however, variability analyses highlighted that upper quartile students significantly improved in both speaking and formal examinations, while the lower quartile cluster failed to show noteworthy forms of progress in speaking, and, formal examination scores exacerbated entirely; concluding therefore that learners’ response to TBLT is governed by their linguistic potential.  The recommendation therefore would be to arrange two separate groupings based on ability for two reasons: (1) assist accelerated acquisition of more proficient students who thrive in a TBLT environment, and, (2) to provide curricular support for struggling students for whom TBLT is not (yet) developmentally appropriate.  ABSTRAKTujuan dari penelitian untuk memperkenalkan Pengajaran Bahasa Berbasis Tugas dalam memberi energi pada kinerja bahasa Inggris yang stagnan pada mahasiswa bisnis tahun kedua (N = 81) yang sedang belajar di sebuah universitas swasta di daerah pinggiran Bangkok. Siswa mengikuti lproses belajar menggunakan TBLT selama satu semester (16 minggu), dan kinerja akhir semester berikutnya dibandingkan dengan pencapaian sebelumnya yang dicapai dalam bentuk pengajaran tradisional menggunakan uji-t (0,05).Secara keseluruhan, TBTL terbukti secara positif mempengaruhi hasil kinerja bila dibandingkan dengan metode tradisional (TBLT: 60,9 = Grade C +; TRAD: 54,93 = Grade C; p [0,0195] = sig <0,05). Meskipun demikian, sebagian besar kemajuan berasal dari peningkatan keterampilan berbicara, karena penilaian dalam domain ini meningkat secara signifikan, sedangkan tidak ada perbedaan signifikan yang diamati dalam ujian formal. Analisis variabilitas menyoroti bahwa siswa kuartil atas secara signifikan meningkat baik dalam ujian berbicara maupun formal, sedangkan cluster kuartil yang lebih rendah gagal menunjukkan bentuk kemajuan penting dalam berbicara, dan, skor ujian formal lebih rendah; oleh karena itu tanggapan pelajar terhadap TBLT diatur oleh potensi linguistik mereka.Karenanya rekomendasi dibagi kedalam dua kelompok terpisah berdasarkan kemampuan karena dua alasan: (1) membantu percepatan akuisisi siswa yang lebih mahir yang berkembang di lingkungan TBLT, dan, (2) untuk memberikan dukungan kurikuler bagi siswa yang berjuang yang menjadi TBLT dimana belum dikembangkan dengan baik. How to Cite: Rudd,  M. (2019). Examining the Effect of Task-Based Language Teaching on University Business Students in Bangkok. IJEE (Indonesian Journal of English Education), 6(1), 30-47. doi:10.15408/ijee.v6i1.11564